The reliability and validity of the Swedish translation of the Vertigo Symptom Scale – short form in a cohort with acute vestibular syndrome - Solmaz Surano; Erik Faergemann; Gabriel Granåsen; Jonatan Salzer (Annals of Medicine)
Background The Vertigo Symptom Scale – short form (VSS–SF) is commonly used to measure dizziness and vertigo over the past month. This study aimed to (1) adapt the VSS–SF for the Swedish population and assess its psychometric properties, and (2) develop a modified version for measuring symptoms in the acute phase of acute vestibular syndrome (AVS).Methods The VSS–SF was translated into Swedish and adapted cross-culturally. Its psychometric properties were evaluated in 86 AVS patients, both in the acute stage (1–7 days from symptom onset) with a modified acute version, and after six weeks of vestibular rehabilitation using the standard VSS–SF. Factor structure, convergent and discriminant validity, and internal consistency were analyzed. Test-retest reliability was assessed at six weeks. Participants were also evaluated with the Dizziness Handicap Inventory (DHI) and balance tests. Controls included 54 healthy participants.Results Exploratory factor analysis revealed a two-factor structure for both versions, corresponding to vertigo-balance (VSS–V) and autonomic-anxiety (VSS–A) subscales. Both versions demonstrated strong factor structures with adequate loadings. Internal consistency was high for the standard version (Cronbach’s alpha 0.76 to 0.87) and for the total and VSS–V subscale of the acute version (0.82 and 0.85, respectively), but poor for the acute VSS–A subscale (0.50). Convergent validity was supported by Spearman’s rank correlations. The discriminative ability was excellent for the acute VSS–SF and VSS–V (AUC 0.98 and 0.99), and acceptable for VSS–A (AUC 0.77). After six weeks, discriminative ability decreased but remained above 0.5. Test-retest reliability at six weeks was excellent for all scales (ICC 0.94, 0.93, and 0.93 for VSS–SF, VSS–V, and VSS–A).Conclusions The VSS–SF was successfully adapted for the Swedish population, including an acute version for early dizziness assessment. Both versions confirmed a robust two-factor structure, with the acute version showing excellent early discriminative ability, particularly for the vertigo-balance dimension. However, the autonomic-anxiety subscale showed weaker psychometric properties, suggesting limited suitability for AVS patients. The adapted scales show promise for clinical use in diagnosing and evaluating dizziness and vertigo in the Swedish population.Trial registration Clinicaltrials.gov Identifier NCT05056324, September 24, 2021. https://clinicaltrials.gov/ct2/show/NCT05056324